2022
DOI: 10.3389/fped.2021.778186
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Improve Safer Sleep Practices in Families With Children Considered to Be at Increased Risk for Sudden Unexpected Death in Infancy: A Systematic Review

Abstract: Background: Advice to families to follow infant care practices known to reduce the risks of Sudden Unexpected Death in Infancy (SUDI) has led to a reduction in deaths across the world. This reduction has slowed in the last decade with most deaths now occurring in families experiencing social and economic deprivation. A systematic review of the literature was commissioned by the National Child Safeguarding Practice Review Panel in England. The review covered three areas: interventions to improve engagement with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(144 reference statements)
0
4
0
1
Order By: Relevance
“…The findings of the original review used to identify interventions concluded that such interventions were moving from ‘information giving’ towards ‘information exchange’ (Ellis et al, 2022). The findings of the current study have provided further insight into this shift, in terms of the specific techniques that are being used to facilitate this change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the original review used to identify interventions concluded that such interventions were moving from ‘information giving’ towards ‘information exchange’ (Ellis et al, 2022). The findings of the current study have provided further insight into this shift, in terms of the specific techniques that are being used to facilitate this change.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a component analysis of 21 safer sleep interventions for families with infants at risk of SUDI examined in a recent systematic review by Ellis et al (2022). The primary studies used various definitions of 'at risk', thus there was variation in the populations who received the safer sleep interventions.…”
Section: Methodsmentioning
confidence: 99%
“…While these programs are effective, their intensive nature means that they are also very costly. A recent systematic review of the literature emphasized the heterogeneity of the existing evidence, need for theoretically grounded models, and called for additional research ( Ellis et al, 2021 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Sabe-se que o aconselhamento familiar a respeito das medidas de sono seguro levou a uma redução dos riscos de Síndrome da Morte Súbita do Lactente e do número de mortes em todo o mundo (Ellis et al, 2022). Sendo assim, é de extrema importância que os profissionais de saúde orientem bem as famílias das crianças menores de 1 ano, principalmente nos primeiros meses de vida do bebê, para que as medidas de prevenção sejam implementadas e haja redução da incidência da SMSL.…”
Section: Medidas Preventivasunclassified